Ways to Develop Motivation for Learning Russian - Mamura, Hakimjanova (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
In this work, methods for increasing motivation to learn Russian as a foreign language among students of technical specialties at an advanced stage of training are considered, which have the greatest potential in current conditions. The work also examines methods and techniques aimed at creating conditions for increasing motivation to learn Russian as a foreign language. It was found that the introduction and integration of information and communication technologies into the educational process have high potential for increasing motivation to learn Russian as a foreign language. Within the framework of this study, the author divides information and communication technologies into two groups of educational tools: technical tools (multimedia complexes) and audiovisual tools (a combination of video and audio materials). The work provides a description and examples of each group. It also highlights the advantages of using these tools in the context of the stated goal. The methods described in the work for increasing motivation to learn Russian as a foreign language among students of technical specialties at an advanced stage of training are effective due to the visibility and demonstration of communicative situations, the formation of a foreign language culture, and the stimulation of the cognitive components of the educational process.